PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP TINGKAT KEPUASAN KONSUMEN LAUNDRY SULTHAN SIMPANG EMPAT - Dea Lisyana Putri; Muhammad Arief Budiman; Lola Malihah; Ahmad Zaini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Laundry Sulthan is a laundry business located in Simpang Empat Village. Every day at least get 30-150 kg of laundry orders. This becomes an attraction to conduct research related to the effect of service quality and price on customer satisfaction. This study aims to determine the effect simultaneously on consumer satisfaction and whether the quality of service and price and the partial effect on consumer satisfaction. The sample in this study is the customer of Laundry Sulthan which was taken as many as 75 people as a sample. Data was collected using a questionnaire and the analysis technique in this study was multiple linear regression. The results of the study indicate that the variables of service quality and price simultaneously affect customer satisfaction with the value of F arithmetic > F table that is 40.559 > 3.124. Then the service quality and price variables also have a partial effect on customer satisfaction with a t count = 6.436 > t table 1.992 for service quality and a t count value = 2.170 and t table 1.992 for price. This shows that the quality of service really has a big influence and some of the influence of price on consumer satisfaction so that it is natural that Laundry Sulthan has many customers every day.